Strategi Hubungan Masyarakat dalam Menangani Keluhan Pelanggan di PT. Pelabuhan Indonesia Persero Cabang Tanjung Balai Asahan - Khoirun Nisa Siregar; Selamat Riadi (Mahesa Research Center, 2025)
This study discusses public relations strategies in handling customer complaints at PT. Port Indonesia (Pelindo) Persero Tanjung Balai Asahan Branch. The focus of this research is how communication strategies are applied in handling complaints to improve customer satisfaction and maintain the company's image. This study uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and document analysis. The results of the study show that responsive communication strategies, service digitization, and interpersonal communication play an important role in handling customer complaints. The implementation of a digital-based complaint management system allows customers to submit complaints more easily and speed up the problem resolution process. In addition, direct interaction between the company and customers creates trust and increases service satisfaction. The conclusion of this study confirms that a good public relations strategy can increase customer loyalty and strengthen the company's reputation as a professional and quality-oriented port service provider